The Study of Teamwork Processes Within the Dynamic Domains of Healthcare: A Systematic and Taxonomic Review - Dinh, Julie V.; Schweissing, Ethan J.; Venkatesh, Akshaya; Traylor, Allison M.; Kilcullen, Molly P.; Perez, Joshua A.; Salas, Eduardo (Frontiers in Communication, 2021)
Teamwork in healthcare is particularly salient in the dynamic domains of critical care: emergency medicine, surgery, and trauma and resuscitation. Within and across these services, in order to provide optimal delivery of health services, teams must be coordinated to provide optimal care. Although many disciplines study teamwork as a result, it is unclear how scholars and clinicians conceptualize, study, and apply these processes. The current systematic review investigates how these fields (1) study teams through the application of a teamwork processes rubric and (2) distinguish themselves from other medical disciplines through the empirical research. We draw upon Marks et al. (2001) and LePine et al. (2008)’s taxonomy of teamwork processes, operationalizing transition, action, and interpersonal processes, to guide this work. Overall, the dynamic domains of literature studied teamwork processes at high rates, relative to other medical fields. Specifically, they were strongly associated with transition and action processes and the content areas of leadership and performance. Given these emphases, research and practical interventions may want to focus on more interpersonal and collaborative approaches in teamwork.